Elemen-Elemen Pembentuk Citra Kota Martapura Kabupaten OKU Timur Berdasarkan Peta Mental Pengamat - Tri Seprianto; Wijayanti Wijayanti; Edi Purwanto (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
One of the most significant factors in achieving a positive image of the city is the selection of image-forming elements. This element's function, location, form, magnitude, uniqueness, and character can all be seen. Martapura is a city that is now undergoing development in order to improve its image. A communal mental map based on Kevin Lynch's idea was employed in this investigation. The goal of this study is to identify the aspects that go into forming the picture of Martapura, which is formed by people's perceptions, experiences, imaginations, and feelings. A qualitative research methodology was applied in this study. This investigation was carried out as a means of discovery. Respondents must freely share their understanding of the things that will reflect the physical elements that make up Martapura's city center in order to understand the physical elements that make up the city center. The physical elements that build the image of Martapura's city center are generated through the function or workings of the things that make up the physical elements of Martapura's city center, according to the findings of the investigation. Physical items such as Tugu Tani, Martapura Market, Merdeka Farmers Park, Merdeka Street, Parai Hotel, Tebat Sari Stadium, and Bank Sumsel Babel are used to organize the physical aspects that make up the image of Martapura City.